Nivel de caries dental según sexo en pacientes adultos atendidos en el centro especializado materno infantil Agüamiro Yurimaguas-2024 - Zegarra Donayre, Miguel Roldan (2024)
The objective of the present study was to evaluate the level of dental caries according to sex in adult patients treated at the Aguamiro Maternal and Child Specialized Center, Yurimaguas. The study was quantitative, descriptive, comparative, because it does not manipulate variables and the events will be described as presented. The sample consisted of 200 adolescent patients treated at the IPRESS Aguamiro. The results show that 69% were female and 31% were male, the highest percentage of decayed pieces per patient was 8 pieces (14%); followed by 7 pieces (13%); 6 and 5 pieces (11%); 2.5% did not have decayed pieces, the highest percentage of lost pieces was 4 pieces (19%); followed by 5 pieces (10.5%); 2 pieces (9.5%); 19% had no lost pieces, the highest percentage of blocked pieces was 1 piece (14%); followed by 2 pieces (13%); 57% did not have blocked parts. In our study, the OPC of the male group was 11.10 and that of the female group was 11.91. No significant differences were found between CPO according to sex (p=0.282). There is a relationship between age and CPO (p=0.000). There is a relationship between age and lost pieces (p=0.000): decayed pieces and filled pieces (p=0.006).